Association of congenital diaphragmatic hernia with extrapulmonary sequestration: A case report - Mostafa Zain; Ahmed Oshiba; Mostafa Kotb; Mohamed Abouheba (Elsevier, 2021)
Pulmonary sequestration (PS) is a non-functioning lesion of lung tissue which lacks communication with the tracheobronchial tree. The incidence of congenital diaphragmatic hernia (CDH) is about 1 in 2500 newborns. While the association of PS with CDH is as high as 30%-40%, the prognosis of their coexistence is unknown. Awareness of the association between pulmonary sequestration with CDH and recognition of the sequestration at the time of the surgery for CDH repair, will prevent the need of a later second operation for a mediastinal mass.